Virkavastuu ja sen rikkominen : tilastoselvitys virkarikoksista v. 1956-1970 - Leppä, Seppo (Kriminologinen tutkimuslaitos, ISSN 0785-7217, 1972)
Summary: Breach of duty : a statistical survey of affenses committed in the discharge of official duties in the years 1956-1970.
Keywords: virkarikokset